North Atlantic Regional Water Resources Study appendix A . [to appendix V] - North Atlantic Regional Water Resources Study Group.; North Atlantic Regional Water Resources Study Coordinating Committee. ([Washington, D.C.] : The Committee, 1972)
Cover title. A. History of study.--B. Economic base.--C. Climate, meteorology and hydrology.--D. Geology and ground water.--E. Flood damage reduction and water management for major rivers and coastal areas.--F. Upstream flood prevention and water management.--G. Land use and land management.--H. Minerals.--I. Irrigation.--J. Land drainage.--K. Navigation.--L. Water quality and pollution.--M. Outdoor recreation.--N. Visual and cultural environment.--O. Fish and wildlife.--P. Power.--Q. Erosion and sedimentation.--R. Water supply.--S. Legal and institutional environment.--T. Plan formulation.--U. Coastal and estuarine areas.--V. Health aspects. Mode of access: Internet.